Porcelain tile with natural travertine texture and preparation method thereof
By adding semi-permeable materials with high content of silica and alumina to the cave stone powder, the mullite crystal structure is generated, which solves the problem of prone to breaking in the processing and handling of cave stone tiles, improves mechanical strength and structural density, and reduces economic losses and water absorption.
Patent Information
- Application Number
- CN202411768059.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-18
AI Technical Summary
Existing cave stone tiles are prone to break during processing and handling, resulting in additional economic losses, and insufficient mechanical strength and denseness in the holes.
By adding a large amount of semi-permeable material to the fog stone powder, the semi-permeable material contains a large amount of silica and alumina, a large amount of mullite crystal structure and skeleton structure are generated, thereby improving the mechanical strength in the hole.
It significantly improves the mechanical strength of porcelain tiles, prevents breakage, reduces economic losses, and improves the structural density at the holes, reduces water absorption, and ensures that porcelain tiles are not easily deformed or fall off during use.
Smart Images

Figure CN119638478A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic tiles, in particular to a ceramic tile with a natural travertine texture and a preparation method thereof. Background Art
[0002] Travertine tiles are widely favored by users because of the various holes and textures on their surface, which give them a very rich sense of layering and three-dimensionality. In order to meet customer needs, the ceramic tile industry has developed a variety of travertine tile manufacturing methods to strive to present the three-dimensional texture of holes in natural travertine and achieve a visual effect that is indistinguishable from the real thing. For example, the Chinese invention patent with application number 201410309410.4, entitled "A method for preparing three-dimensional travertine tiles with holes", adds pore-forming materials to conventional fabrics, so that when the tiles are fired, the pore-forming materials are decomposed by heat to produce gas, thereby forming holes in the fabric layer. In this technology, the pore-forming material is composed of 5-10% ball clay, 10-20% low-temperature frit powder, 10-20% graphite powder, 10-15% sodium carbonate, 20-30% calcium carbonate powder, and 5-10% polishing waste residue. Although the ball clay in the pore-forming material contains more alumina and silica, the proportion of ball clay is low, which makes the alumina and silica content in the pore-forming material lower. During the firing process, fewer mullite crystals are formed in the holes, which makes the mechanical strength of the holes lower, resulting in easy breakage of tile products during processing and transportation, causing additional economic losses. Summary of the invention
[0003] The purpose of the present invention is to solve the above problems and shortcomings, and to provide a natural travertine texture porcelain tile and a preparation method thereof, wherein a large amount of semi-permeable material is added to the travertine powder, and the semi-permeable material contains a large amount of silicon dioxide and aluminum oxide, so that more mullite crystal structures and skeleton structures can be generated at the holes, so that the holes have good mechanical strength, thereby effectively preventing the porcelain tile product from breaking and reducing additional economic losses. The porcelain tile provided by the present invention has very good mechanical strength, which can greatly reduce accidental losses caused by product breakage.
[0004] The technical solution of the present invention is achieved as follows: a method for preparing a natural travertine texture porcelain tile, comprising preparing a mixed travertine powder, wherein the mixed travertine powder is prepared by mixing travertine powder and gypsum, and the characteristics are: the raw materials of the travertine powder include: 65-75 parts of semi-permeable material and 25-35 parts of calcite in parts by weight; the chemical composition of the semi-permeable material in parts by weight is as follows: SiO 2 Content 65%~75%, Al 2 O 3 Content 12% ~ 20%, CaO content 0.1% ~ 0.4%, MgO content 0.5% ~ 2%, K 2O content 0.8% to 3%, Na 2 O content 3% to 6%, Fe 2 O 3 Content 0.1%~0.4%, TiO 2 The content is 0.01% to 0.08%, and the loss on ignition is 3% to 8%. The raw materials of the mixed travertine powder include, by weight: 95 to 98 parts of travertine powder and 2 to 5 parts of gypsum.
[0005] Furthermore, it also includes fabric base powder, which is distributed by a distribution vehicle. The fabric base powder and mixed travertine powder are distributed from different material pipes of the distribution vehicle respectively, and the mixed travertine powder is distributed on the fabric base powder to form a fabric layer, and the mixed travertine powder is located on the top of the fabric layer.
[0006] Furthermore, the particle gradation of the mixed travertine powder in terms of weight percentage is: ≤1.5% on a 20-mesh sieve, 40% to 50% on a 40-mesh sieve, and ≤3% under a 100-mesh sieve.
[0007] Furthermore, the gypsum is raw gypsum.
[0008] Furthermore, the weight percentage of the mixed travertine powder in the entire fabric layer is 2% to 7%.
[0009] Furthermore, after the mixed travertine powder is fired, an independent hole texture or crack texture is formed on the top of the surface layer; the thickness of the surface layer is 2-6 mm, and the depth of the hole texture or crack texture is 0.1-1.0 mm.
[0010] Beneficial effects of the present invention:
[0011] Firstly, the present application adds a large amount of semi-permeable material to the travertine powder used for making holes, and the semi-permeable material has silicon dioxide and aluminum oxide as main components. In this way, during the firing process of the brick blank, the silicon dioxide in the semi-permeable material combines with the aluminum oxide to form mullite crystals, and the excess silicon dioxide is converted into quartz, which together with the mullite crystals forms a skeleton at the hole, so that the hole has very good mechanical strength and is not easy to break; at the same time, the structural density of the hole is also good, which can effectively prevent moisture from penetrating into the interior of the porcelain tile, ensure that the porcelain tile has a very low water absorption rate, and make the porcelain tile not easy to deform or fall off during use.
[0012] Secondly, a small amount of MgO is added to the semipermeable material as an emulsifier to form a translucent glass phase during the firing process. After firing, the areas around the holes appear translucent and permeable, thereby better reflecting the three-dimensional hierarchical structure of the holes and further improving product quality.
[0013] Then, calcite is used as the main pore-forming raw material. On the one hand, the pore-forming raw material is single, so the number and size of the holes can be easily controlled by directly controlling the amount of calcite added. On the other hand, after calcite is decomposed by heat, the generated CaO can combine with SiO2 at high temperature to generate high-strength CaSiO3, further improving the mechanical strength of the holes; at the same time, it can also improve the light transmittance of the holes after firing and enhance the layered three-dimensional effect of the holes.
[0014] Finally, during the firing process of porcelain tiles, gypsum can decompose into gaseous water at low temperatures and SO at high temperatures. 2 In this way, by making holes twice at low temperature and high temperature, a three-dimensional layered hole structure with holes within holes can be formed, which is closer to the hole structure of natural volcanic rock and closer to the texture of natural travertine.
[0015] The present invention also provides a porcelain tile prepared by the above method, the surface glossiness of the porcelain tile is 15 to 35°, which restores the unique matte decorative effect of natural travertine to the greatest extent; the rupture modulus is ≥35MPa, has very good mechanical properties, and is very suitable for making large-scale travertine tile products; and the water absorption rate is ≤0.5%, and it is not easy to deform or fall off due to water absorption during use. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic diagram of the process flow of the present invention.
[0017] Figure 2 It is a schematic diagram of the layered structure of the porcelain tile of the present invention.
[0018] Figure 3 The product of the present invention Figure 1 .
[0019] Figure 4 The product of the present invention Figure 2 . DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings of the present invention.
[0021] like Figure 1 As shown, a method for preparing a ceramic tile with a natural travertine texture includes preparing a mixed travertine powder, wherein the mixed travertine powder is prepared by mixing travertine powder and gypsum. In order to achieve the purpose proposed by the present invention, the raw materials of the travertine powder include: 65-75 parts of semi-permeable material and 25-35 parts of calcite in parts by weight; the chemical composition of the semi-permeable material in parts by weight is as follows: SiO 2 Content 65%~75%, Al 2 O3 Content 12% ~ 20%, CaO content 0.1% ~ 0.4%, MgO content 0.5% ~ 2%, K 2 O content 0.8% to 3%, Na 2 O content 3% to 6%, Fe 2 O 3 Content 0.1%~0.4%, TiO 2 Content 0.01% ~ 0.08%, loss on ignition 3% ~ 8%; the raw materials of the mixed travertine powder in parts by weight include: 95-98 parts of travertine powder, 2-5 parts of gypsum. In this way, the semi-permeable material uses silicon dioxide and aluminum oxide as the main components to make the holes have more mullite crystal structures and the skeleton formed by silicon dioxide and mullite crystal structures, so that the holes have very good mechanical strength; at the same time, the holes can also be made densely structured, which can prevent moisture from penetrating into the interior of the porcelain tile, with a very low water absorption rate, and the holes are translucent around, which can better present the three-dimensional layering of the holes and the inside of the holes, achieving a realistic simulation effect, greatly improving product quality. The gypsum is preferably raw gypsum, which contains more water. When the bricks are fired, more water can be decomposed, thereby generating a richer hole structure on the fabric layer.
[0022] Furthermore, the preparation method of the present invention also includes a fabric base powder, which is distributed by a distribution vehicle, and the fabric base powder and the mixed travertine powder are respectively distributed from different material tubes of the distribution vehicle, and the mixed travertine powder is distributed on the fabric base powder to form a fabric layer, and the mixed travertine powder is located on the top of the fabric layer; since the mixed travertine powder is distributed by a separate material tube, a separate mixed travertine powder texture can be formed on the top of the fabric layer, and after high-temperature firing, an independent hole texture or crack texture is formed on the top of the fabric layer; preferably, the thickness of the fabric layer is 2-6mm, and the depth of the hole texture or crack texture is 0.1-1.0mm, so that there is no hole structure inside the fabric layer, thereby greatly reducing the influence of the hole structure on the strength of the porcelain tile product, which is beneficial to improving the structural strength of the porcelain tile product; and the hole texture or crack texture is not limited by the texture pattern of the porcelain tile itself, and can be interspersed between multiple textures in the fabric layer, so that the hole distribution is more natural, the hole shape is more flexible and changeable, and closer to the texture of natural travertine.
[0023] In the present application, due to the precise application of the mixed travertine powder, the mixed travertine powder can be fully utilized, thereby greatly saving the amount of the mixed travertine powder. The weight percentage of the mixed travertine powder in the entire fabric layer in the present application is 2% to 7%.
[0024] Furthermore, the particle gradation of the mixed travertine powder in terms of weight percentage is: ≤1.5% on a 20-mesh sieve, 40% to 50% on a 40-mesh sieve, and ≤3% under a 100-mesh sieve. In this way, through different particle gradations, the particles of the mixed travertine powder are large and small, thereby forming hole textures or crack textures of varying sizes and depths on the top surface of the porcelain tile body.
[0025] Furthermore, the present invention also includes a base material layer located at the bottom of the fabric layer, and the fabric layer and the base material layer are stamped together to obtain a green body, and the obtained green body strength is ≥0.4MPa. In this way, the green body has good structural strength, thereby preventing the green body from being damaged during transportation. The bottom material can be made of the same material as the fabric base powder, or a different material. In order to make the base material layer and the fabric layer tightly pressed to form a whole, the moisture content of the fabric base powder is 5.3% to 5.8%, and the moisture content of the base material of the base material layer is slightly higher, 6.7% to 7.3%.
[0026] Furthermore, the green bricks are sent to a drying chamber for drying, and the moisture content of the dried bricks is 0.3% to 0.5%, and the strength is ≥ 0.8 MPa. In this way, since the moisture content of the bricks is low, the cracking caused by uneven heating inside and outside the bricks during the firing process can be prevented, and the mechanical strength of the bricks after drying is high, which can also effectively prevent the bricks from being mechanically damaged during transportation.
[0027] Further, the dried bricks are sent to a kiln for firing to form travertine porcelain tiles, with the firing temperature being 1150-1200°C and the firing time being 55-65 minutes. The method adopts a low-temperature fast firing process, which can effectively reduce the energy consumption of the product.
[0028] Furthermore, the fired travertine porcelain tile surface is processed in sequence using the following steps: using a 400-mesh common grinding block to grind the travertine porcelain tile surface → using a 600-mesh elastic grinding block to grind the travertine porcelain tile surface → using an 800-mesh elastic grinding block to grind the travertine porcelain tile surface → using a 400-mesh fiber brush to grind the travertine porcelain tile surface → performing super-brightness treatment on the travertine porcelain tile surface → applying matte wax water on the travertine porcelain tile surface. After the above surface treatment, the surface of the travertine porcelain tile product is smooth and delicate, and a visual brick surface light feeling similar to stone is obtained.
[0029] like Figure 2 , 3As shown, the travertine porcelain tile prepared in the present application is composed of a base material layer and a surface material layer from bottom to top, wherein the top of the surface material layer is provided with hole textures or crack textures of varying sizes and depths, with holes within holes, and the structure of these hole textures or crack textures is very close to the hole structure of natural volcanic travertine, and its surface glossiness is 15 to 35°, restoring the unique matte decorative effect of natural travertine to the greatest extent; its rupture modulus is ≥35MPa, and its water absorption rate is ≤0.5%, and it has very good structural strength and low water absorption rate, and is more stable and durable to use.
[0030] The present invention will be further described below in conjunction with specific embodiments.
[0031] Embodiment 1:
[0032] like Figure 1 As shown, the specific production steps in this embodiment are as follows:
[0033] S1: Preparation of mixed travertine powder, firstly, 70 parts by weight of semipermeable material and 30 parts by weight of calcite are mixed to prepare travertine powder, then 96 parts by weight of travertine powder and 4 parts by weight of gypsum are mixed to prepare mixed travertine powder, and then the mixed travertine powder is prepared into mixed travertine powder according to a conventional powder preparation method, wherein the particle gradation of the mixed travertine powder in terms of weight percentage is: ≤1.5wt% on 20 mesh sieve, 40% to 55% on 40 mesh sieve, ≤3% under 100 mesh sieve, and the moisture content is 5.3wt% to 5.8wt%. The gypsum is raw gypsum, which contains more water. When the brick is fired, more water can be decomposed, thereby generating a richer pore structure on the surface layer.
[0034] The chemical composition of the semi-permeable material is as follows: SiO 2 Content 72.74%, A1 2 0 3 Content 16.1%, Ca0 content 0.33%, MgO content 0.98%, K 2 0 content 1.02%, Na 2 0 content 4.25%, Fe 2 O 3 Content 0.33%, TiO 2 The content is 0.06% and the loss on ignition is 4.19%; the raw material formula of the semi-permeable material in this embodiment is composed of 35% sodium sand, 19.5% high sodium sand, 11% potassium sodium water abrasive, 13% medium white ball clay, 3% ball clay, 4.5% washed mud, 8% bentonite, 4% black mud and 2% white talc.
[0035] S2: Preparation of basic fabric powder. The basic fabric powder used in this embodiment is conventional fabric powder in the ceramic tile industry.
[0036] S3: Preparation of base material powder. The base material powder used in this embodiment is conventional base material powder in the ceramic tile industry.
[0037] S4: laying and blank making, laying and stamping the mixed travertine powder, base powder for fabric and base powder for base material by conventional process to obtain green blanks; wherein the base powder for fabric and the mixed travertine powder are respectively put into different hoppers of a laying vehicle and laid through different material pipes to form a fabric layer, wherein the mixed travertine powder is arranged on the top of the fabric layer, and the weight percentage of the mixed travertine powder in the whole fabric layer is 7%; the base powder for base material forms a base material layer and is placed at the bottom of the fabric layer; the green blank strength is 0.6MPa to prevent the green blank from being damaged during transportation.
[0038] S5: Drying: The green bricks are sent to a drying chamber for drying. The moisture content of the dried bricks is 0.3% to 0.5%, and the strength is 1.0 MPa. Since the moisture content of the bricks is low, the cracking caused by uneven heating inside and outside the bricks during the firing process can be prevented. The mechanical strength of the bricks after drying is high, and the bricks can be effectively prevented from being mechanically damaged during transportation.
[0039] S6: Firing: sending the dried bricks into a kiln for firing to form travertine porcelain tiles, controlling the firing temperature to be 1150-1200°C, and the firing time to be 55-65 minutes.
[0040] S7: grinding and polishing, the fired travertine porcelain tile surface is processed in the following steps: using a 400-mesh ordinary grinding block to grind the travertine porcelain tile surface → using a 600-mesh elastic grinding block to grind the travertine porcelain tile surface → using an 800-mesh elastic grinding block to grind the travertine porcelain tile surface → using a 400-mesh fiber brush to grind the travertine porcelain tile surface → super-brightening the travertine porcelain tile surface → applying matte wax water on the travertine porcelain tile surface. After the above surface treatment, the surface of the travertine porcelain tile product is smooth and delicate, and a visual brick surface light feeling similar to stone is obtained.
[0041] like Figure 2 , 3 As shown, the travertine porcelain brick prepared by the present invention has holes of different depths and sizes on the surface, and small holes are embedded in the big holes. The luster is delicate and soft, and it has the texture of natural travertine.
[0042] Embodiment 2:
[0043] The steps and parameters in this embodiment are the same as those in the first embodiment, except that the weight percentage of the mixed travertine powder in the entire fabric layer in this embodiment is 5%.
[0044] Embodiment three:
[0045] The steps and parameters in this embodiment are the same as those in the first embodiment, except that the weight percentage of the mixed travertine powder in the entire fabric layer in this embodiment is 3%.
[0046] Comparative Example:
[0047] This embodiment is a comparative example, and each step and parameter are the same as those of the first embodiment, except that no mixed travertine powder is added to the fabric layer in this embodiment.
[0048] The ceramic tile products prepared in Examples 1, 2, 3 and Comparative Example were tested for performance, and the test results are shown in the following table:
[0049]
[0050] It can be seen from the above test data that, compared with the comparative example, with the increase in the amount of mixed travertine powder added, the rupture modulus performance of the prepared porcelain tile decreases, but it also meets the index requirements for dry-pressed ceramic tiles in GB / T4100-2015, and has good mechanical strength, which can effectively prevent the product from breaking during processing or transportation; it can also be seen from the above table that with the increase in the amount of mixed travertine powder added, the water absorption rate of the porcelain tile does not increase much. This is because the structure of the holes is relatively dense, which can effectively prevent moisture from penetrating into the interior of the porcelain tile. In this way, during use, the product can be effectively prevented from being deformed or falling off due to water absorption, so that the product of the present invention has a longer service life.
[0051] The present invention makes the surface of the porcelain tile of the present invention present a matte texture through grinding, polishing and coating of matte wax water, thereby better reflecting the unique decorative effect of natural travertine.
Claims
1. A method for preparing a ceramic tile with a natural travertine texture, comprising preparing a mixed travertine powder, wherein the mixed travertine powder is prepared by mixing travertine powder and gypsum, and characterized in that: The raw materials of the travertine powder include, by weight: 65-75 parts of semipermeable material and 25-35 parts of calcite; the chemical composition of the semipermeable material, by weight percentage, is as follows: SiO2 content 65%-75%, Al2O3 content 12%-20%, CaO content 0.1%-0.4%, MgO content 0.5%-2%, K2O content 0.8%-3%, Na2O content 3%-6%, Fe2O3 content 0.1%-0.4%, TiO2 content 0.01%-0.08%, and loss on ignition 3%-8%; the raw materials of the mixed travertine powder include, by weight: 95-98 parts of travertine powder and 2-5 parts of gypsum.
2. The preparation method according to claim 1, characterized in that: It also includes fabric base powder, which is distributed by a distribution vehicle. The fabric base powder and mixed travertine powder are distributed from different material pipes of the distribution vehicle respectively, and the mixed travertine powder is distributed on the fabric base powder to form a fabric layer, wherein the mixed travertine powder is located on the top of the fabric layer.
3. The preparation method according to claim 1, characterized in that: The particle size distribution of the mixed travertine powder in terms of weight percentage is: ≤1.5% on a 20-mesh sieve, 40% to 50% on a 40-mesh sieve, and ≤3% under a 100-mesh sieve.
4. The preparation method according to claim 1, characterized in that: The gypsum is raw gypsum.
5. The preparation method according to claim 2, characterized in that: The weight percentage of the mixed travertine powder in the entire fabric layer is 2% to 7%.
6. The preparation method according to claim 5, characterized in that: After the mixed travertine powder is fired, an independent hole texture or crack texture is formed on the top of the surface layer; the thickness of the surface layer is 2-6 mm, and the depth of the hole texture or crack texture is 0.1-1.0 mm.
7. The preparation method according to claim 2, characterized in that: It also includes a base material layer located at the bottom of the surface layer. The surface layer and the base material layer are punched together to obtain a green body, and the green body is sent to a drying chamber for drying. The moisture content of the dried brick body is 0.3% to 0.5%, and the strength is ≥0.8MPa.
8. The preparation method according to claim 7, characterized in that: The dried bricks are sent to a kiln for firing to obtain travertine porcelain bricks. The firing temperature of the kiln is 1150-1200° C., and the firing time is 55-65 minutes.
9. The preparation method according to claim 8, characterized in that: The surface of the travertine porcelain tile is treated in sequence using the following procedures: use a 400-mesh ordinary grinding block to grind the surface of the travertine porcelain tile → use a 600-mesh elastic grinding block to grind the surface of the travertine porcelain tile → use an 800-mesh elastic grinding block to grind the surface of the travertine porcelain tile → use a 400-mesh fiber brush to grind the surface of the travertine porcelain tile → perform super-bright cleaning treatment on the surface of the travertine porcelain tile → apply matte wax water on the surface of the travertine porcelain tile.
10. A porcelain tile, characterized in that: The porcelain tile is prepared by the preparation method according to any one of claims 1 to 9, and the surface glossiness of the porcelain tile is 15 to 35°, the rupture modulus is ≥35MPa, and the water absorption rate is ≤0.5%.
Citation Information
Patent Citations
Method for preparing three-dimensional cavitation travertine ceramic tile
CN104045375A